An Interesting Cause of Hyperandrogenemic Hirsutism - Murat Atmaca; İsmet Seven; Rıfkı Üçler; Murat Alay; Veysi Barut; Yaren Dirik; Yasin Sezgin (Case Reports in Endocrinology)
Mild clinical signs of hyperandrogenism such as hirsutism may appear during the menopausal transition as part of the normal aging process, but the development of frank virilization suggests a specific source of androgen excess. We report a case of a 68-year-old woman with signs of virilization that had started 6 months before. Clinical analyses revealed high levels of serum testosterone for a postmenopausal woman. Pelvic MRI and abdomen CT showed no evidence of ovarian and adrenal tumor. Postmenopausal hyperandrogenism can be the result of numerous etiologies ranging from normal physiologic changes to ovarian or rarely adrenal tumors. Our patient was found to have iatrogenic hyperandrogenism. This condition is rarely reported cause of virilization.